Consumers’ views on utilizing social media influencers in organization’s CSR communication - Korpiala, Ella (2022)
Corporate social responsibility (CSR) has become a global norm to observe and there is an increasing interest in utilizing social media influencers (SMIs) in organization’s CSR communication. Further research on consumer perspective of CSR communication utilizing SMIs is required to understand the challenges and possibilities in influencing perceptions of target audiences. The aim of this study is to understand how consumers perceive CSR communication that utilizes SMIs. The research was done with qualitative methods. In total of eight individual semi- structured interviews were conducted from April to May 2022. The participants were chosen with a snowball sampling method and the requirement for participance was following SMIs. The interviews included a method of participant-included elicitation (PIE), in which example videos of a CSR campaign were shown to awaken consumer’s thoughts. The campaign had an environmental topic of reducing the eutrophication of the Baltic Sea. The campaign was a collaboration between a public sector organization Helsingin seudun ympäristöpalvelut and two Finnish SMIs. The data was analysed with thematic analysis and the findings suggest three themes to describe consumer perceptions: SMI’s role in consumer’s everyday life, evaluation of the CSR initiative and the organization as well as the evaluation of the SMI. Findings of the study align with previous research. Consumers seem to have narrow views on organization as the collaboration’s manager and SMI as the CSR communication’s distributor. Factors that created perceptions were related to skepticism along with SMI characteristics, such as authenticity, expertise, similarity, and brand- influencer fit. The study adds to previous research that public sector organizations in CSR collaborations are perceived the same as commercial organizations, unless the organization is well-known and appreciated by the consumer. It was also found that SMI’s values and published content must align with the consumer’s values for the CSR information to be perceived as credible.